PEMBERDAYAAN IJTIHAD WAQI'I BAGI DA’I DALAM MASYARAKAT ISLAM - Syukur, Abdul (Universitas Islam Negeri Raden Intan Lampung, 2015)
Ijtihad is a technical term of Islamic law that describesthe process of making a legal decision by independentinterpretation of the legal sources, the Qur’an and theSunnah. Ijtihad waqi'i in the Islamic dakwah is veryimportant for the challenges facing the Muslim world.Ijtihad is also important to find arguments for thedakwah, and responding to the dynamic developmentof Muslim civilization, as well as provide solutions totheir problems. In addition, ijtihad also brings benefitsin developing ukhuwah based on local wisdom inLampung. In its dakwah, da’i of the Nahdlatul Ulamaorganization in Lampung, support the success ofijtihad waqi'i, such as the empowering of theintellectual preachers, their awareness andcompetencies to synergize the textual messages withcontextual one, based on local wisdom. This articlewill further elaborate on these topics.